Smartphone Abuse Amongst Adolescents: The Role of Impulsivity and Sensation Seeking - Pérez de Albéniz Garrote, Gloria; Rubio, Laura; Medina Gómez, Begoña; Buedo-Guirado, Cristina (Frontiers in Psychology, 2021)
Adolescence is the stage of development where the reward and emotional regulation systems are yet to be adjusted and where most excessive behaviors start, like smartphone abuse. In addition, in this evolutionary period adolescents are more susceptible to behavioral changes through specific interventions or educational programs. Thus, it is fundamental to analyze the personality profile of those adolescents showing excessive mobile phone usage to properly approach later prevention strategies. Impulsivity is one of the most repeated variables associated with teenage addictions, although it has been observed that not all impulsive behaviors need to be detrimental. The aim of this study is to analyze how impulsivity affects smartphone addiction directly, but also indirectly, by assessing its association with sensation seeking variables (thrill and adventure seeking, experience seeking, disinhibition and boredom susceptibility) which are in turn decisive when using these technologies improperly. The sample was made up of 614 adolescents aged 13-18 attending secondary education from Burgos, Spain. Dickman Impulsivity Inventory, Sensation Seeking Scale, and Ad-hoc questionnaire on adolescent self-perception as to smartphone use were applied. Results show that 41.4% of participants admit to abusing smartphones sometimes, while 18.3% admit to abusing them more frequently and 24% to, at least ever, having defined themselves as smartphone addicts. Stepwise regression analysis revealed that gender (female), dysfunctional impulsivity and sensation seeking (disinhibition and thrill and adventure seeking) evidence 15.7% of variance in smartphone abuse. In addition, sensation seeking (thrill and adventure seeking, disinhibition and boredom susceptibility) were found to mediate the relationship between dysfunctional impulsivity and smartphone abuse. Therefore, dysfunctional impulsivity was directly connected with teenage smartphone abuse, but also had an indirect stronger association through thrill and adventure seeking, disinhibition and boredom susceptibility.